2003
DOI: 10.1258/135763303321159684
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with teledermatology services

Abstract: We collected data on patient satisfaction with the use of teledermatology services. During a 27-month study, a single dermatologist saw a total of 321 patients via telemedicine. The patients completed 483 surveys, although not all questions were answered on all surveys. There was a high level of satisfaction among patients using teledermatology: 88% of 258 respondents said that they were satisfied with their telemedicine session. In terms of the eight questions on the questionnaire, 84% of the responses were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 10 publications
9
35
0
1
Order By: Relevance
“…Youth completed a satisfaction questionnaire at the end of the evaluation. This 11-item questionnaire was based on questionnaires described in the telemedicine literature [17]. Three items covered technical aspects of the Interactive Videoteleconferencing (IVTC) transmission and seven items covered clinical aspects of the experience.…”
Section: Methodsmentioning
confidence: 99%
“…Youth completed a satisfaction questionnaire at the end of the evaluation. This 11-item questionnaire was based on questionnaires described in the telemedicine literature [17]. Three items covered technical aspects of the Interactive Videoteleconferencing (IVTC) transmission and seven items covered clinical aspects of the experience.…”
Section: Methodsmentioning
confidence: 99%
“…58 The median satisfaction rating (on a scale of 0-10) was also higher for the teledermatology group (9.6 vs 9.0, P = .03). Of the 3 studies without a comparison group, the reported satisfaction ratings were 44%, 46 88%, 64 and 92%. 65 Overall.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 99%
“…[3][4][5][6][7][8] Store-and-forward teledermatology using digital cameras has also recently been associated with reduced patient wait times, high patient satisfaction, [9][10][11][12][13] promising diagnostic reliability, [14][15][16][17] and clinical outcomes similar to conventional, faceto-face clinical care. 18,19 To date, however, the vast majority of teledermatology studies and projects have focused on industrialized nations, whereas the potential need for teledermatology may be most profound in the developing world.…”
mentioning
confidence: 99%